Analysis and Standardization of Indicators of Technical Skills of First Secondary Level Teachers - Eskandari, Farzad; Abolmaali Alhosseini, Khadijeh; Dortaj, Fariborz; Bagheri, Fariborz (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of this research was to analyze and standardize the indicators of technical skills among first secondary level teachers in Karaj in 2021. Methods and Materials: The research method was descriptive and contextual. The study population comprised all first secondary level teachers across the four districts of Karaj, from which a sample of 329 teachers was selected using a cluster random sampling method. A researcher-developed questionnaire consisting of 27 items was utilized. Data analysis was conducted using confirmatory factor analysis with the aid of Amos software. Findings: The findings indicate that each component of the technical skills questionnaire, which includes consulting skills, teaching skills, classroom management skills, evaluation skills, and information and communication technology skills, demonstrated favorable internal consistency. Conclusion: Consequently, it was concluded that each item possesses sufficient power to measure the components of teachers' technical skills, and each component effectively measures the broader construct of teachers' technical skills.